Kajian Kepentingan Keupayaan Kepimpinan Kontraktor G7 dalam Mengurus Projek Pembinaan - Zakaria, Balqis; Omar, Roshartini; Sarpin, Norliana; Shafii, Haryati (Research in Management of Technology and Business, 2021)
Leaders are the most important assets in an organization that plays a role in determining the direction and goals of the organization. Nevertheless, leadership issues in the development industry have an impact on project management. Individual leadership in a company is often with the ups and downs of a project, thus someone who must be measured for a development project can be implemented more systematically. The objective of this study is to examine the level of the importance of contractor leadership in managing development projects, identify best practices that should be practiced by contractors, and identify measures to improve contractor leadership in managing development projects. The study was conducted with a quantitative method that uses a questionnaire instrument with a population of G7 contractor respondents in Selangor and targeted G7 contractors who received the 4 and 5 Star in Contractor Ability and Capability Assessment Program (SCORE). A total of 30 respondents representing 55% of the study sample have provided feedback on the questionnaire. The data obtained from the questionnaire were analyzed using Statistical Packages for Social Science (SPSS) version 20.0. The findings of the study prove that level of the importance of contractor leadership in managing development projects is high when the majority of the mean score reaches 4.50. The study also identifies the best practice for leaders is to respect other individuals and society and it reaches the highest mean value among other practices. Next, this study explores measures to strengthen the capability of leaders by finding advice from mentors or veterans from the industry. Consequently, the findings obtained at the end of this study are significant in making current and future generation leaders aware of leadership capabilities.